Strategi Pemasaran Perusahaan Logistik - Wulandari, Diah Ayu; Setyawati, Aswanti (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2018)
The purpose of the study was to assess the effect of marketing strategy of the companyâs performance and the role of competition environment in moderating the marketing strategy of the companyâs performance. The MRA (Moderated Regression Analysis) was used as the analyzing method. The result shows that there is a significant and positive effect of the marketing strategy of the companyâs performance (r = 0, 912), and a significant and positive effect of the logistics competition environment of the companyâs performance (r = 0, 955). The role of competition environment in moderating the negative relation between marketing strategy and companyâs performance since the competition environment comes from outside and could threaten the companyâs marketing and decrease the performance.